Common Mind Habits of Sulaimani Polytechnic University Students - Ayub Khosrow Nader (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The aim of this study was to investigate the common mental habits of the students of Sulaymaniyah Technical University. The number of students was 210 students who were selected from the students of institutes and colleges at Sulaimaniyah Technical University. To achieve the objectives of the study, the results of the study indicate that the four mental habits in the sample of the study (sometimes) are found in them in general. There are no statistically significant differences between the results of males and females. Students in different departments of colleges and institutes have close mental habits Pretty much. This study concluded with a number of recommendations calling for attention to the four habits of the mind through training programs and to give the attention of university officials to the importance of developing the habits of the mind and work on their development among university students, conducting studies aimed at other mental habits and with other samples of students.